Modernization of system risk-management in commercial banks of Russia - A. I. Vinogradov (Путеводитель предпринимателя)
Now in the Russian commercial banks there is an objective need for modernization of system of a risk management. The growing arrears among borrowers of bank, on the one hand, and absence in a credit portfolio of commercial bank of the innovative and investment credits more than three years, with another - testify to imperfection of model of a risk management in a banking system and emphasize requirement of its expeditious improvement.